External parasites of raptors (Falconiformes and Strigiformes): identification in an ex situ population from Mexico - De Oliveira, Jaqueline B. (2011)
Raptorial birds harbor a variety of ectoparasites and the mayority of them are host specific. The aim of this study was to identify the ectoparasites of captive birds of prey from Mexico, as well as to verify their impact in the health of infested birds. Raptorial birds were confiscated and kept in captivity at the Centro de Investigación y Conservación de Vida Silvestre (CIVS) in Los Reyes La Paz, Mexico State. Seventy-four birds of prey (66 Falconiformes and eigth Strigiformes) of 15 species were examined for the presence of ectoparasites. We examined both juvenile and adult birds from both sexes. The overall prevalence was 16.2%; 66.7% of raptors were infested with a single type of external parasite. Lice were the most prevalent ectoparasites (91.7%), followed by feather mites and fleas (8.3%). Degeeriella fulva (72.7%), Craspedorrhynchus sp. (45.4%) and Strigiphilus aitkeni (9.1%) (Ischnocera, Philopteridae) were recovered from wings, head and neck regions of red-tailed hawk (Buteo jamaicensis), Swainson’s hawk (B. swainsoni), Harris’s hawk (Parabuteo unicinctus) and Barn owl (Tyto alba). Low lice infestation level was observed. Nymphs and females of feather mites Kramerella sp. (Pterolichoidea, Kramerellidae) were recovered solely from Barn owl (T. alba); while one Caracara (Caracara cheriway) was infested by the sticktight flea Echidnophaga gallinacea (Siphonaptera, Pulicidae). No clinical signs were observed in any infested bird. Probably the periodic use of organophosphorates was responsible of the low prevalence and lice infestation levels. The diversity of external parasites illustrates the importance of detailed revision of incoming and long-term captive raptors as part of responsible captive management. Five new hosts and geographic records are presented.